What Goes Around Comes Around: Knowledge Hiding, Perceived Motivational Climate, and Creativity - Černe, Matej; Nerstad, Christina G. L.; Dysvik, Anders; Škerlavaj, Miha (Academy of Management Journal, 2014)
Knowledge hiding prevents colleagues from generating creative ideas, but it may also have negative consequences for the creativity of a knowledge hider. Drawing on social exchange theory, we propose that when employees hide knowledge, they trigger a reciprocal distrust loop in which coworkers are unwilling to share knowledge with them. We further suggest that these effects are contingent on motivational climate, in such a way that the negative effects of an individual's hiding knowledge on his/her own creativity are enhanced in a performance climate and attenuated in a mastery climate. A field study of 240 employees nested in 34 groups revealed a negative relationship between knowledge hiding and knowledge hiders' creativity as well as a moderating role of a mastery climate. Study 2 replicated these findings in an experimental study of 132 undergraduate students, testing a reciprocal distrust loop and comparing it with an alternative intrapsychic explanatory process based on situational regulatory focus. Implications for practice and future research are discussed.